2017
DOI: 10.1007/s11999-016-4966-1
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Difference in Revision Risk Between Metal and Ceramic Heads on Highly Crosslinked Polyethylene Liners?

Abstract: Background The most common bearing surface used among primary THAs worldwide is a metal or ceramic femoral head that articulates against a highly crosslinked ultrahigh-molecular-weight polyethylene (HXLPE) acetabular liner. Despite their widespread use, relatively little is known about the comparative effectiveness of ceramic versus metal femoral heads with respect to risk of revision and dislocation as well as the role of head size in this relationship. Questions/purposes The purpose of this study was to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 37 publications
(33 reference statements)
2
16
0
1
Order By: Relevance
“…These databases should not be confused with smaller registries that typically collect data prospectively for a particular diagnosis (diabetes) or procedure (joint replacement) (7,8). While smaller registries often record disease or procedure-specific outcomes such as functional scores, patient-satisfaction, and radiographic reports; largevolume databases contain more generalized information such as demographics, comorbidities, cost, length of stay, as well as procedure and diagnosis codes.…”
Section: Large-volume Databasesmentioning
confidence: 99%
“…These databases should not be confused with smaller registries that typically collect data prospectively for a particular diagnosis (diabetes) or procedure (joint replacement) (7,8). While smaller registries often record disease or procedure-specific outcomes such as functional scores, patient-satisfaction, and radiographic reports; largevolume databases contain more generalized information such as demographics, comorbidities, cost, length of stay, as well as procedure and diagnosis codes.…”
Section: Large-volume Databasesmentioning
confidence: 99%
“…9 , 14 , 32 However, other studies have shown no difference in all-cause revision between ceramic and metal (CoCr) heads when used in combination with a highly cross-linked liner. 33 While theoretical models comparing cost of metal toxicity work-up in the US health care system may justify a switch to ceramic heads, this has remained theoretical. 34 Because there can be a significant cost differential with ceramic (compared to metal) heads, a wholesale switch to ceramic femoral heads to decrease the risk of corrosion may not be justified as this may result in an economic burden to socialized health-care systems.…”
Section: Discussionmentioning
confidence: 99%
“…Hip arthroplasty is being applied at increasing frequency worldwide. Various materials are used to prolong the survival of the components in parallel with increasing human life expectancy 2 , 3 . In hip arthroplasty applications throughout the world, there is an increasing frequency of selection of ceramic head and ceramic liner as osteolysis occurs at a lower rate and at a later stage 1 .…”
Section: Discussionmentioning
confidence: 99%
“…In hip arthroplasty applications throughout the world, there is an increasing frequency of selection of ceramic head and ceramic liner as osteolysis occurs at a lower rate and at a later stage 1 . Fracture is one of the most commonly observed complications in patients where ceramic materials are used 2 . However, new ceramic materials are more resistant 1 .…”
Section: Discussionmentioning
confidence: 99%